Design for Revitalizing Historical Identity: Case Study Zakho Old Bazaar, Kurdistan Region, Iraq - Halima Ahmad Othman (International Journal of Urban Design and Development, 2025)
A town in northern Kurdistan, near the border of Iraq, Turkey, and Syria converge, Zakho was rural center and regional marketplace. The city exhibits remarkable sites dating to various eras, including Dalal bridge and Al-Qeshla, an ancient site with significant truistic attraction. Zakho has been a center of religious diversity, dynasty to Muslims, Christians, and Jews, which has significantly influenced the city’s rich urban environs and architectural heritage. The old bazaar’s architecture reflects multiple historical eras. Zakho old bazaar is located in the area where the river splits into two branches, forming an island. The historical value of the old bazaar relies in its unique architectural elements, materials, and crafts which formed specific cultural and architectural identity for the city. Due to the strategic location, the city had prolific urbanization process toward all directions. The old bazaar left abandoned and subjected to deterioration. In 2022, an initiative project was issued as a competitive design proposal and a detailed budget plan for revitalization of Zakho old bazar. This research focuses in the design phase of the old Zakho bazaar exploring sustainable urban design principles to make the design ready to be implemented. A contemporary design was proposed with special focus on the city’s culture and historical identity restoring the cherished cultural values and repurpose the abandoned commercial activities as initiative attempt for future development in the lavish old site.
Keywords: Architecture; Design; Heritage; cultural; historical city; identity; old bazaar